The Role of the DPRD in Creating a Clean Government from KKN (Pematangsiantar City Study) - Zakaria Tambunan; Tamaulina Br. Sembiring; Ali Yusran Gea (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the role of the Regional People's Representative Council (DPRD) of Pematangsiantar City in creating a clean government from the practice of Corruption, Collusion, and Nepotism (KKN). This study uses a descriptive-analytical method with a normative and empirical juridical approach through literature studies and field observations. The results of the study show that the Pematangsiantar City DPRD has carried out its supervisory function through work meetings, program evaluations, field inspections, and the use of interpellation rights and the right of inquiry. However, the effectiveness of supervision is still constrained by limited recommendatory authority, barriers to access to public information, and overlapping authority with other supervisory institutions. This study concludes that strengthening the role of the DPRD in realizing a clean government requires firm regulatory support, capacity building and institutional integrity, and active participation of the community.